POLIGAMI LIAR MENURUT UNDANG-UNDANG NO. 1 TAHUN 1974 - Rudi Rudi; Septi Pratiwi Suci (Istinbath | Jurnal Penelitian Hukum Islam, 2018)
One of the principles of marriage according to Law no. 1 year 1974 is a monogamous marriage. But the principle of monogamy is not absolute. One of the conditions for a husband who wants to marry more than one is to be fair and get the approval of the first wife and apply to the Religious Courts. But the realization is still a lot of irregularities that occur in the community about polygamy. Many of the people who do illegal polygamy without the permission of the Religious Courts for various reasons. The impact of polygamy is also felt by the first wife that her rights become neglected because of the second wife. Polygamy procedures and rights and obligations of husbands who are polygamy or have more than one wife are regulated in detail in Law no. 1 of 1974 on Marriage and Compilation of Islamic Law (KHI), the two laws are a positive law in force in Indonesia.